2018
DOI: 10.2147/bctt.s137508
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on triptorelin in the treatment of premenopausal women with early-stage breast cancer

Abstract: Endocrine treatment represents the cornerstone of endocrine-sensitive premenopausal early breast cancer. The estrogen blockade plays a leading role in the therapeutic management of hormone receptor-positive breast cancer together with surgery, radiotherapy, and selective antiestrogen treatments. For several years, selective estrogen receptor modulators, such as tamoxifen, have represented the mainstay of therapy. The role of amenorrhea has been extensively elucidated in the past year: the benefit observed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
(82 reference statements)
0
3
0
2
Order By: Relevance
“…Discovering the prominent role of CTGF during breast cancer invasion by modifying cell adhesion, ECM degradation and FN1 expression, we wanted to test if CTGF can be targeted and elucidated molecular mechanism by which CTGF can be repressed to suppress cell dissemination and colonization at distant sites. We found that GnRH agonist Triptorelin, which is in clinical use for ovarian function suppression of premenopausal breast cancer with high clinical risk of recurrence 28 , and was demonstrated to reduce breast cancer invasion 37 , reduced CTGF expression in mesenchymal transformed breast cancer in a dose-dependent manner. Furthermore, we found that CTGF was downregulated by Triptorelin treatment in TNBC cells.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Discovering the prominent role of CTGF during breast cancer invasion by modifying cell adhesion, ECM degradation and FN1 expression, we wanted to test if CTGF can be targeted and elucidated molecular mechanism by which CTGF can be repressed to suppress cell dissemination and colonization at distant sites. We found that GnRH agonist Triptorelin, which is in clinical use for ovarian function suppression of premenopausal breast cancer with high clinical risk of recurrence 28 , and was demonstrated to reduce breast cancer invasion 37 , reduced CTGF expression in mesenchymal transformed breast cancer in a dose-dependent manner. Furthermore, we found that CTGF was downregulated by Triptorelin treatment in TNBC cells.…”
Section: Resultsmentioning
confidence: 93%
“…Suppression of ovarian function is part of therapy of endocrine-sensitive premenopausal early and advanced hormone receptorpositive breast cancer. Triptorelin, a GnRH agonist, revealed clinical benefit in high-risk patients by suppressing ovarian steroids and it has been investigated in attempt to preserve ovarian function during chemotherapy in young female patients 28 . GnRH receptor is expressed in 50-64% of all human breast cancers [29][30][31][32][33] .…”
Section: Ctgf Differentially Regulates Potential Drivers Of Invasion mentioning
confidence: 99%
“…1). Они активно применяются при лечении злокачественных новообразований в области репродуктивной системы и гинекологических заболеваний, связанных с нарушением эндокринной регуляции [4][5][6][7][8][9].…”
Section: Development Of Identifi Cation Test Methods For Triptorelin unclassified
“…1). They are widely used in the treatment of malignant tumours of the reproductive system and gynecological diseases associated with endocrine regulation disorders [4][5][6][7][8][9].…”
Section: заключениеmentioning
confidence: 99%
“…Например, в молекулах бусерелина, гозерелина и трипторелина присутствует прототропная таутомерия в 4-замещенном имидазоле гистидинового фрагмента. Эти соединения являются синтетическими аналогами гонадолиберина и активно применяются при лечении злокачественных новообразований в области репродуктивной системы и гинекологических заболеваний, связанных с нарушением эндокринной регуляции [47][48][49][50][51]. 4 протонного обмена N-H…N в интегральную скорость миграции протона до критического уровняскорость прототропной таутомерии замедляется.…”
Section: внутримолекулярные перегруппировкиunclassified